Deeper Roots of Transactional Programming. - Green, Alastair (Communications of the ACM, 2014)
A letter to the editor is presented in response to the article "Democratizing Transactional Programming," by Vincent Gramoli and Rachid Guerraoui in the January 2014 issue.